1997
DOI: 10.1021/jo970642d
|View full text |Cite
|
Sign up to set email alerts
|

A One-Pot Condensation of Pyrones and Enals. Synthesis of 1H,7H-5a,6,8,9-Tetrahydro-1-oxopyrano[4,3-b][1]benzopyrans

Abstract: Condensation of various 6-substituted 4-hydroxypyrones 1 with 1-cyclohexenecarboxaldehydes in the presence of L-proline in ethyl acetate gave high yields of substituted 1H, 7H-5a,6,8,9-tetrahydro-1-oxopyrano[4,3-b][1]benzopyrans. The reaction presumably occurs via the 1,2-addition of the pyrone with the aldehyde followed by dehydration and then cyclization through a 6Π electrocyclic process. A remarkable asymmetric induction was obtained from a stereogenic center (C4) of the cyclohexenecarboxaldehyde [such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(45 citation statements)
references
References 15 publications
1
41
0
3
Order By: Relevance
“…For small R 1 groups, it was proposed that equilibration between axial and equatorial substituents should favor the intermediate with minimum A 1,3 strain, and equatorial approach of the oxygen atom during the ring closure would lead to the major isomer. Similar transformations with other electrophiles have been reported, [168][169][170][171] and an approach in which the source of chirality is carbohydrate-derived has also been described. 172 8p Electrocyclizations ( p 8 a ) 8p/6p Electrocyclization cascades.…”
Section: Thermal Reactions 4p Electrocyclizations ( P 4 a )supporting
confidence: 54%
“…For small R 1 groups, it was proposed that equilibration between axial and equatorial substituents should favor the intermediate with minimum A 1,3 strain, and equatorial approach of the oxygen atom during the ring closure would lead to the major isomer. Similar transformations with other electrophiles have been reported, [168][169][170][171] and an approach in which the source of chirality is carbohydrate-derived has also been described. 172 8p Electrocyclizations ( p 8 a ) 8p/6p Electrocyclization cascades.…”
Section: Thermal Reactions 4p Electrocyclizations ( P 4 a )supporting
confidence: 54%
“…1. The focused library of tricyclic pyrones was prepared according to our published procedures (Hua et al, 1997;Hua et al, 2003).…”
Section: Synthesis Of Compound Librariesmentioning
confidence: 99%
“…First, sterically congested α,β-unsaturated iminium salts such as 13 can impede the formal [3 ϩ 3] cycloaddition, although Jonassohn's [12] work provides some assurance. Secondly, and more significantly, despite reports by Jonassohn [12] and Hua, [13] as well as our own results, [16] the ability to control the stereochemistry of the angular methyl group at C-6a through this key formal [3 ϩ 3] cycloaddition reaction was quite speculative. Scheme 10 However, because the 6π-electron electrocyclic ring-closure of the respective 1-oxatriene 55 was found to be reversible, [15,22] a favorable diastereoselectivity could be achieved leading to the thermodynamically more stable isomer 12, in which the C-6a methyl group is in the β-position (Scheme 10).…”
Section: Synthetic Problems and Solutionsmentioning
confidence: 66%
“…Subsequently, Hua reported an elegant study [13] that preceded our communication. [11,14] In their study, shown in Scheme 5, cyclic enals were employed in view of their inter- www.eurjoc.org est in arisugacin A (6).…”
Section: Synthetic Problems and Solutionsmentioning
confidence: 99%
See 1 more Smart Citation